Development of an open source membrane steady state simulator - Zainal Abidin, Shahrul Azman (2004)
A membrane steady state simulator based on an open source concept is discussed. It is believe that this way of developing software will overcome weaknesses posed by available commercial membrane simulators. The application provides a cost effective state of the art tool for membrane modeling and object oriented design and its usage allows for easy incorporation of specific developments either open source or proprietary. This paper presents the components require to produce an open source membrane steady state simulator. This approach of development differs significantly from a close black-box approach. Several membrane models using the simulator will be elaborated and compared with literature results.